2015
DOI: 10.1101/gr.189225.115
|View full text |Cite
|
Sign up to set email alerts
|

Identifying genomic changes associated with insecticide resistance in the dengue mosquito Aedes aegypti by deep targeted sequencing

Abstract: The capacity of mosquitoes to resist insecticides threatens the control of diseases such as dengue and malaria. Until alternative control tools are implemented, characterizing resistance mechanisms is crucial for managing resistance in natural populations. Insecticide biodegradation by detoxification enzymes is a common resistance mechanism; however, the genomic changes underlying this mechanism have rarely been identified, precluding individual resistance genotyping. In particular, the role of copy number var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
211
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(232 citation statements)
references
References 80 publications
20
211
1
Order By: Relevance
“…The involvement of detoxification complex enzymes in both resistance and defense to pyrethroids has been documented in several arthropod species, including mosquitoes61112. Among them, cytochromes P450 (CYPs), carboxylesterases (CCEs), glutathione S-transferases (GSTs), UDP-glucuronosyl transferases (UGTs) enzymes, as well as ABC transporters were found differentially expressed between resistant and susceptible strains to pyrethroids1617183031. Likewise, induced up-regulation of detoxifying genes was found in resistant individuals exposed to pyrethroids, such as in the mosquito Anopheles gambiae 30, the cattle tick Rhipicephalus (Boophilus) microplus 32 or the mosquito Culex quinquefasciatus 2425, as well as in susceptible individuals, such as in Panonychus citri 19, Liposcelis bostrychophila 20, and Melita plumulosa 21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of detoxification complex enzymes in both resistance and defense to pyrethroids has been documented in several arthropod species, including mosquitoes61112. Among them, cytochromes P450 (CYPs), carboxylesterases (CCEs), glutathione S-transferases (GSTs), UDP-glucuronosyl transferases (UGTs) enzymes, as well as ABC transporters were found differentially expressed between resistant and susceptible strains to pyrethroids1617183031. Likewise, induced up-regulation of detoxifying genes was found in resistant individuals exposed to pyrethroids, such as in the mosquito Anopheles gambiae 30, the cattle tick Rhipicephalus (Boophilus) microplus 32 or the mosquito Culex quinquefasciatus 2425, as well as in susceptible individuals, such as in Panonychus citri 19, Liposcelis bostrychophila 20, and Melita plumulosa 21.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic studies that have focused on single time-points showed that the exposure of individuals to toxicants induces up-regulation of several genes, while several others are down-regulated161718192021. However, these are single snapshots of the defense response that do not allow us to know if and how the differentially expressed genes are modulated during toxicant exposure.…”
mentioning
confidence: 99%
“…aegypti involve target site alterations and metabolic resistance, comprising altered activity of enzymes from three superfamilies, esterases (CCEs), glutathione-s-transferases (GSTs) and cytochrome P450s (CYP450s), although several other enzyme families are likely to be involved [12]. Overexpression of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…). Furthermore, the traditional control method – pesticide – is both indiscriminate and thwarted by the multiple cases of pesticide resistance in Aedes mosquitoes recently reported 8, 9 .…”
Section: Introductionmentioning
confidence: 99%